THE INVARIANT SPLITTING FORMALISM IN GENERAL RELATIVITY - Gladush, V. D.; Konoplya, R. A. (Одеські астрономічні публікації, 2017)
The invariant splitting method of a pseudo-Riemanian manifold on arbitrarynumber of sections has been constructed in the present work.